Blockade of the Notch Signaling Pathway Promotes M2 Macrophage Polarization to Suppress Cardiac Fibrosis Remodeling in Mice With Myocardial Infarction - Li, Zhi; Nie, Miao; Yu, Liming; Tao, Dengshun; Wang, Qiang; He, Yuanchen; Liu, Yu; Zhang, Yuji; Han, Hongguang; Wang, Huishan (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction is regarded as a serious ischemic heart disease on a global level. The current study set out to explore the mechanism of the Notch signaling pathway in the regulation of fibrosis remodeling after the occurrence of myocardial infarction. Firstly, experimental mice were infected with recombination signal binding protein J (RBP-J) shRNA and empty adenovirus vector, followed by the establishment of myocardial infarction mouse models and detection of cardiac function. After 4 weeks of myocardial infarction, mice in the sh-RBP-J group were found to exhibit significantly improved cardiac function relative to the sh-NC group. Moreover, knockdown of RBP-J brought about decreased infarct area, promoted cardiac macrophages M2 polarization, reduced cardiac fibrosis, and further decreased transcription and protein expressions of inflammatory factors and fibrosis-related factors. Furthermore, down-regulation of cylindromatosis (CYLD) using si-CYLD reversed the results that knockdown of RBP-J inhibited fibrogenesis and the release of inflammatory factors. Altogether, our findings indicated that blockade of Notch signaling promotes M2 polarization of cardiac macrophages and improves cardiac function by inhibiting the imbalance of fibrotic remodeling after myocardial infarction.